Antierosive profile of an experimental solution based on antioxidants from Passiflora edulis on initial dentin erosion lesions - Ronaldo Matheus Araújo MARVÃO; Tayanne Laíse da Rocha Prixan LOUZEIRO; Maria Carolina Sidonio ALVES; Kalinca Furtado de OLIVEIRA; Gabriel Tadashi Valente do Couto GOTO; Gabriela Carvalho Santos FERNANDES; Antonia Patricia Oliveira BARROS; Milton Carlos KUGA; Cristiane de Melo ALENCAR (Universidade Estadual Paulista, 2024)
Abstract Introduction The non-carious degradation of the dentin matrix is a natural process throughout life; however, when associated with the presence of excessive acidic substances, it leads to lesions in dental structures. Objective This study developed an experimental solution based on antioxidant polyphenols from the yellow passion fruit seed (Passiflora edulis) and assessed its preventive potential on eroded dentin. The experimental polyphenolic solution was obtained from passion fruit seeds through drying and cold pressing. Material and method Thirty samples of bovine cervical root dentin were acquired and randomized into three groups (n=10): G1 - distilled water; G2 - experimental solution of phenolic antioxidants from passion fruit; G3 - Commercial anti-erosion toothpaste. Erosive cycling and treatment were conducted over 3 days. Subsequently, non-contact 3D confocal microscopy was employed to measure volumetric (Sa) and linear (Ra) roughness, as well as erosive wear. A one-way ANOVA/Tukey test was performed (α=0.05). Result The G2 group had lower Ra and Sa values compared to the other groups and demonstrated the lowest erosive wear in µm compared to G1 and G3. Conclusion: The experimental solution based on antioxidant polyphenols from Passiflora edulis showed promising performance on eroded dentin in this investigation. Nevertheless, further research is required to establish its effectiveness and potential use in developing a new product.